Circulating N-formylmethionine and metabolic shift in critical illness: a multicohort metabolomics study - Sigurdsson, Martin Ingi; Kobayashi, Hirotada; Amrein, Karin; Nakahira, Kiichi; Rogers, Angela J.; Pinilla-Vera, Mayra; Baron, Rebecca M.; Fredenburgh, Laura E.; Lasky-Su, Jessica A.; Christopher, Kenneth B. (Critical Care, 2022)
Background Cell stress promotes degradation of mitochondria which release danger-associated molecular patterns that are catabolized to N -formylmethionine. We hypothesized that in critically ill adults, the response to N -formylmethionine is associated with increases in metabolomic shift-related metabolites and increases in 28-day mortality. Methods We performed metabolomics analyses on plasma from the 428-subject Correction of Vitamin D Deficiency in Critically Ill Patients trial (VITdAL-ICU) cohort and the 90-subject Brigham and Women’s Hospital Registry of Critical Illness (RoCI) cohort. In the VITdAL-ICU cohort, we analyzed 983 metabolites at Intensive Care Unit (ICU) admission, day 3, and 7. In the RoCI cohort, we analyzed 411 metabolites at ICU admission. The association between N -formylmethionine and mortality was determined by adjusted logistic regression. The relationship between individual metabolites and N -formylmethionine abundance was assessed with false discovery rate correction via linear regression, linear mixed-effects, and Gaussian graphical models. Results Patients with the top quartile of N -formylmethionine abundance at ICU admission had a significantly higher adjusted odds of 28-day mortality in the VITdAL-ICU (OR, 2.4; 95%CI 1.5–4.0; P = 0.001) and RoCI cohorts (OR, 5.1; 95%CI 1.4–18.7; P = 0.015). Adjusted linear regression shows that with increases in N -formylmethionine abundance at ICU admission, 55 metabolites have significant differences common to both the VITdAL-ICU and RoCI cohorts. With increased N -formylmethionine abundance, both cohorts had elevations in individual short-chain acylcarnitine, branched chain amino acid, kynurenine pathway, and pentose phosphate pathway metabolites. Conclusions The results indicate that circulating N -formylmethionine promotes a metabolic shift with heightened mortality that involves incomplete mitochondrial fatty acid oxidation, increased branched chain amino acid metabolism, and activation of the pentose phosphate pathway. Graphic Abstract